Integrative review of older adult loneliness and social isolation in Aotearoa/New Zealand. (4th March 2017) - Wright‐St Clair, Valerie A; Neville, Stephen; Forsyth, Vanessa; White, Lindsey; Napier, Sara
Abstract : Objective: To conduct an integrative review of empirical studies of loneliness for older people in Aotearoa/New Zealand. Loneliness is a risk factor for older people's poor physical and cognitive health, serious illness and mortality. A national survey showed loneliness rates vary by gender and ethnicity. Methods: A systematic search of health and social science databases was conducted. Of 21 scrutinised articles, nine were eligible for inclusion and subjected to independent quality appraisal. One qualitative and eight quantitative research articles were selected. Results: Reported levels and rates of loneliness vary across age cohorts. Loneliness was significantly related to social isolation, living alone, depression, suicidal ideation, being female, being Māori and having a visual impairment. Qualitatively, older Korean immigrants experienced loneliness and social isolation, along with language and cultural differences. Conclusion: Amongst older New Zealanders loneliness is commonly experienced by particular ethnic groups, highlighting a priority for targetted health and social services.